Use of Lumen-Apposing Stents for the Treatment of Postsurgical Fluid Collections: A Case Series and a Review of Literature - Priyanka Priyanka; William Hsueh; John Nasr (Case Reports in Gastrointestinal Medicine)
Lumen-apposing metal stents (LAMS) use in gastrointestinal endoscopy has been on the rise for various indications for the last few years. Currently, LAMS is a well-established treatment for post-pancreatitis peri-pancreatic fluid collections and walled-off necrosis (WON), but it is still not a standard of care in the treatment of post-surgical fluid collections (PSFC). Most of the earlier studies for treatment of PSFC utilized double pigtail plastic stents (DPS). We present a series of 3 cases where LAMS was successfully used for PSFC drainage. The cases include a patient with perigastric abscess after Whipple’s procedure, a case of peri-pancreatic collection after distal pancreatectomy, and a patient with peri-pancreatic fluid collection after right partial hepatectomy and splenectomy due to lacerations from a motor vehicle accident.